Genetic Algorithm based Fuzzy Logic Controller for Optimal Charging-Discharging of Energy Storage in Microgrid applications - Faisal M.; Hannan M.A.; Ker P.J.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Computer circuits; Energy storage; Fuzzy logic; Genetic algorithms; Membership functions; Microgrids; Particle swarm optimization (PSO); Secondary batteries; Water treatment; Battery state of charge; Charging/discharging; Fuzzy logic controllers; Microgrid; Optimal charging; Power; Renewable technology; States of charges; Storage systems; Swarm optimization; Controllers